Status Gizi dan Pengetahuan Remaja Putri dalam Upaya Pencegahan Anemia Defisiensi Besi - Fatmawati, Tina Yuli; Julaecha, Julaecha; Efni, Nel (Jurnal Akademika Baiturrahim Jambi, 2024)
Anemia is a public health problem in Indonesia that can be experienced by all age groups, from toddlers to the elderly. Adolescent girls are prone to suffer from iron deficiency anemia because they lose a lot of blood during menstruation. Anemia in adolescent girls can affect physical growth and reproductive health. The aim of this research is to determine the relationship between knowledge and nutritional status of adolescent girls on efforts to prevent iron deficiency anemia. This research design uses an analytical observational method with a cross sectional approach which aims to see the relationship between each variable studied. The research sample consisted of 60 people.  The instruments used were questionnaires to determine knowledge variables and anthropometric measurements using scales and microtoices to see nutritional status. The data were analyzed using univariate and bivariate analysis. The research results showed that there was no relationship between knowledge and nutritional status on efforts to prevent iron deficiency anemia in adolescent girls at SMP N 8 Jambi City, Jambi City. It is recommended that young women increase their knowledge about anemia and pay attention to the type and frequency, quantity and diversity of food so that they can prevent anemia.